(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Global communication among individuals all over the globe has become a reality as the global Internet has evolved through time. With the growth of the Internet of Things, sentient, human-to machine, and device conversations have all been transformed into interaction among everyone and everything that is related to people, individual, and device communications (IoT). As a result, the Internet of Things has being enabled to capture all aspects of human life, including safety and security, medical treatment, recycle, ecological monitoring, and so on. This article discusses the relevance of IoT technologies in the field of schooling in terms of boosting the effectiveness of teaching and learning. We look at it from several angles, such as computer science training, medical, distance learning, consumers environmental schooling, and so on. The Internet of Things (IoT) in schooling has radically changed educational institutions by allowing Web connections amongst real things, sensors, and controllers. By embedding detectors in products and merging cloud computing, virtual reality, wearables, and big information in this platform, many aspects of the learning atmosphere may be observed and analyzed to provide relevant information. It has also created a new link between people and the environment in educational institutions.